CHOOSING NOT TO CHOOSE IS A CHOICE: A NOBLE LESSON OF THE BADUY PEOPLE IN INTERPRETING NEUTRAL CHOICES IN VOTING IN GENERAL ELECTIONS - Lestari, Ratih (Indonesia Law Review, 2023)
Democracy can simply be interpreted as "the government of the people by the people and for the people". One of the pillars of democracy is elections, which are a means of forming power based on popular sovereignty. With elections, democracy can be run through a system that guarantees citizens the freedom to actively participate in politics. Article 22E paragraph (1) of the 1945 NRI Constitution, elections are held directly, publicly, freely, and confidentially. This means that every citizen who is already qualified has the right and freedom to choose and be selected and get the same treatment in accordance with applicable regulations. Political participation in society is interpreted differently, especially in the principle of freedom of choice. This article aims to explain how the Baduy people interpret neutrality by not participating in voting as a noble choice in the voting system in a democracy. The purpose of writing is to project a perspective on how the law should interpret the choices of how to vote in a democracy as a cultural property that must be respected. The research was conducted using a series of sociological procedures to support the process of analysis and legal reflection on the way Baduy people determine attitudes in voting mechanisms in the democratic process of elections.